Ocorrência de Mannheimia haemolytica e de Pasteurella multocida em ovinos sadios e com enfermidade respiratória - Viana, L. [UNESP]; Gonçalves, R.C. [UNESP]; Oliveira Filho, J.P. [UNESP]; Paes, A.C. [UNESP]; Amorim, R.M. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2007)
Frequency of Mannheimia haemolytica and Pasteurella multocida in the respiratory tract of lambs in the region of Botucatu, SP, Brazil, was studied. Nasopharingeal and oropharingeal swabs were obtained from 262 animals: 180 from healthy and 82 from animals with respiratory diseases. M. haemolytica was the most prevalent (47%), followed by the association of M. haemolytica and P. multocida (27%), and P. multocida (11%). Animals with respiratory disease presented higher occurrence of P. multocida in the nasopharynx as compared to healthy animals (P<0.05). No significant difference in isolation rate of M. haemolytica, P. multocida, and association of these microorganisms in the oropharynx of healthy and affected animals was observed.
Mannheimia haemolytica and Pasteurella multocida occurrence in healthy and affected lambs
Keywords: ovino; Mannheimia haemolytica; Pasteurella multocida; doenças respiratória; lamb; Mannheimia haemolytica; Pasteurella multocida; respiratory diseases